Rasmussen’s Encephalitis: A Report of a Tunisian Pediatric Case and Literature Review - Hedia Klaa; Thouraya Ben Younes; Hanene Benrhouma; Sonia Nagi; Aida Rouissi; Ichraf Kraoua; Ilhem Ben Youssef-Turki (Case Reports in Neurological Medicine)
Rasmussen’s encephalitis (RE) is a rare progressive inflammatory disease of the central nervous system. It is characterized by unilateral hemispheric atrophy, pharmacoresistant focal seizures, and progressive neurological deficit. The exact etiopathogenesis still remains unknown. Brain imaging plays an important role in diagnosis and follow-up. Fluctuation of lesions in brain imaging was reported in few cases. Herein, we report an additional pediatric case of Rasmussen encephalitis with fluctuating changes in brain MRI.